Determining factors of sports dropout of young scholars: a cross-sectional analysis in the 8–13 year age group - Pisaniello, Andrea; Figus, Alessandro; Digennaro, Simone; Spulber, Diana (Frontiers in Sports and Active Living, 2024)
This article investigates the phenomenon of sports abandonment among young scholars aged between 8 and 13 years. Regardless of the growing awareness of the importance of sport and physical activity during childhood and adolescence, this theme must be adequately explored in the scientific literature.Our study addresses this gap through a cross-sectional research design, tracking and analyzing data from a cohort of young athletes over one year. The main objective of our study is to identify the determinants leading to sports dropout in this specific age group.We looked at several possible causes through a multivariate analysis, including social pressures, parental expectations, time conflicts, physical and psychological stress, and lack of enjoyment. The results show a significant attrition rate, with psychosocial factors emerging as the most influential in determining whether a young person will continue or stop their participation in sport.Furthermore, our study highlights the importance of targeted interventions and preventive strategies that promote a positive, inclusive, and balanced sports environment for adolescents. These interventions can be particularly effective when implemented by coaches, parents and others involved in youth sports education.Finally, this paper discusses the implications of the findings for sports professionals, physical educators, and public policy makers. It highlights the need for more effective support policies and innovative pedagogical approaches to promote sporting persistence during adolescence. Our findings can serve as a starting point for further research in this field, helping to build a future where young people can enjoy the many benefits of sport and physical activity.